Experimental study on triple pass solar air heater with thermal energy storage for drying mint leaves. (2018) - Kesavan, S.; Arjunan, T.V.
Solar dryer is used to preserve agricultural products, save energy consumption and reducing environmental impact. A new type of solar collector has been designed and tested. This study deals with the design of a modular drying system consisting of two functional units, namely a triple pass flat plate air collector with thermal storage and a drying chamber. The flat plate collector is 2 m long, 1 m wide and 0.1 m deep, and incorporates absorber and thermal energy storage unit. Air flows between two glazing during first pass then in the opposite direction through the absorber during second pass and finally through the spaces between units of thermal energy storage and bottom plate into drying chamber. The experiments are conducted for drying mint leaves and the results show that considerable improvement in drying time and moisture removal. It is concluded that the design is compact, sufficiently simple and gives a high thermal performance.